Collagen Membranes Functionalized with 150 Cycles of Atomic Layer Deposited Titania Improve Osteopromotive Property in Critical-Size Defects Created on Rat Calvaria - Faverani, Leonardo P. [UNESP]; Astaneh, Sarah Hashemi; Costa, Monique Gonçalves da [UNESP]; Delanora, Leonardo A. [UNESP]; Lima-Neto, Tiburtino J. [UNESP]; Barbosa, Stéfany [UNESP]; Ariani, Maretaningtias Dwi; Takoudis, Christos; Sukotjo, Cortino (MDPI, 2023)
The membranes used in bone reconstructions have been the object of investigation in the field of tissue engineering, seeking to improve their mechanical strength and add other properties, mainly the osteopromotive. This study aimed to evaluate the functionalization of collagen membranes, with atomic layer deposition of TiO2 on the bone repair of critical defects in rat calvaria and subcutaneous biocompatibility. A total of 39 male rats were randomized into four groups: blood clot (BC), collagen membrane (COL), COL 150—150 cycles of titania, and COL 600—600 cycles of titania. The defects were created in each calvaria (5 mm in diameter) and covered according to each group; the animals were euthanized at 7, 14, and 28 days. The collected samples were assessed by histometric (newly bone formed, soft tissue area, membrane area, and residual linear defect) and histologic (inflammatory cells and blood cells count) analysis. All data were subjected to statistical analysis (p < 0.05). The COL150 group showed statistically significant differences compared to the other groups, mainly in the analysis of residual linear defects (1.5 ± 0.5 × 106 pixels/µm2 for COL 150, and around 1 ± 0.5 × 106 pixels/µm2 for the other groups) and newly formed bone (1500 ± 1200 pixels/µm for COL 150, and around 4000 pixels/µm for the others) (p < 0.05), demonstrating a better biological behavior in the chronology of defects repair. It is concluded that the collagen membrane functionalized by TiO2 over 150 cycles showed better bioactive potential in treating critical size defects in the rats’ calvaria.
Keywords: atomic layer deposition; membrane functionalization; osseointegration; titanium dioxide